Lulu Sinagtala and the city of noble warriors - Gail D. Villanueva (New York : Harper Collins Publishers., 2024)
"Discovering that the creatures and deities of Tagalog myth are real when her mom is kidnapped, Lulu Sinagtala is drawn into a centuries-long war that threatens to throw the whole universe into chaos while trying to save her mom with her newfound powers"-- Provided by publisher.
Keywords: Mothers and daughters -- Juvenile fiction; Kidnapping -- Juvenile fiction; Magic -- Juvenile fiction; Animals, Mythical -- Juvenile fiction; Mythology, Philippine -- Juvenile fiction; Imaginary wars and battles -- Juvenile fiction